Peran serta siswa dan guru dalam pengelolaan lingkungan hidup: Studi kasus di SMA Negeri 1 Anggi Kabupaten Pegunungan Arfak - Saiba, Seblon; Tanujaya, Benidiktus; Sabariah, Vera (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aims to determine the role of students and teachers in increasing environmental awareness and their role in reducing inefficient resources. This research is expected to encourage all students and teachers to participate actively in all school activities, with a particular focus on forming an environmentally friendly school. The study was conducted using a qualitative approach with a descriptive type of research that aims to describe a symptom/event that occurs. Data were collected through observation, interviews, and questionnaires employing a Likert scale with five answer options. The findings revealed that students and teachers at SMA Negeri 1 Anggi, Gunung Arfak Mountains Regency, West Papua Province play a pivotal role in environmental management within their educational institution.